Etyczne uregulowania kontaktów studentów medycyny z firmami farmaceutycznymi w Stanach Zjednoczonych - Makowska, Marta (Annales. Etyka w Życiu Gospodarczym, 2014)
The involvement of the pharmaceutical industry in medical education can be seen as something completely natural. Who better than the producer of the med-icine would know how the drug was developed, how the process of it being au-thorized for sale proceeded, and what the side effects of it are? Today in the United States, more and more colleges are implementing strong pharmaceutical conflict-of-interest policies. Interaction between students and medical school staff with these companies is undesirable, because they share marketing materi-als more often than honest data, and their representatives use various ways to influence these current and future physicians during their meetings.This article will describe research which shows what pharmaceutical mar-keting directed at students looks like in the USA – its character, frequency, and potential impact on future medical decisions. Also, ways of regulating interac-tion between medical schools, their staff and students and the pharmaceutical industry will be expressed. Guidelines of the Association of American Medical Colleges, the Institute of Medicine and the American Medical Student Associa-tion will be described. At the end, questions about their influence on reality and whether medical schools’ policies can be an effective barrier for pharmaceutical marketing on medical schools will be asked.